1981
DOI: 10.1002/aic.690270213
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of surface flow phenomenon of adsorbed gases by hopping model

Abstract: The mechanism of surface flow of adsorbing gas molecules through the porous adsorbent is interpreted, and a new hopping model is derived by separately taking into account the hopping behaviors of monolayer and multilayer molecules. The reported experimental results containing the data measured here are correlated well. Finally, some considerations are given to the two experimental constants appearing in the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 12 publications
2
70
0
Order By: Relevance
“…Yang et al 39 and Okazaki et al 40 proposed modified equations including many physical parameters, such as Qst, the latent heat of vaporization, and the activation energy of the liquid viscosity of the adsorbate. In this study, Eq.…”
Section: Hopping Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 39 and Okazaki et al 40 proposed modified equations including many physical parameters, such as Qst, the latent heat of vaporization, and the activation energy of the liquid viscosity of the adsorbate. In this study, Eq.…”
Section: Hopping Modelmentioning
confidence: 99%
“…[38][39][40] Higashi et al 38 proposed the following simple function to explain the concentration dependence of Ds.…”
Section: Hopping Modelmentioning
confidence: 99%
“…The hopping model (Weaver and Metzner, 1966) would be unsatisfactory if the mobile fraction of admolecules is significant, as in most of the cases here. In addition, its dependence on surface coverage must be found empirically (Okazaki et al, 1981). Finally, these methods are incomplete because they ignore the interaction between bulk and surface flows (Thakur et al, 1980).…”
Section: Calculatmdmentioning
confidence: 98%
“…The object of this paper is tc demonstrate and explain the occurrence of a dual breakthrough phenomenon for single-component adsorption, which had been observed by Cagliostro et al (1985), in terms of a moving-boundary model for the rapid transport of an adsorbed vapor. The occurrence of this dual breakthrough phenomenon is shown to permit the separation of surface and volume diffusivities, which has not previously been possible (Riekert, 1985).The surface flux of lighter gases has been characterized by surface hopping models and spreading pressure models (Okazaki et al, 1981), but the dynamics of adsorption of condensable vapors have been little characterized to date. Flood et al (1952) found that surface transport of strongly adsorbed organic vapors was highest for the lowest partial pressures of the adsorbate, corresponding to the steepest region of their adsorption isotherm, and attributed this to a greater thermodynamic driving force for surface spreading.…”
mentioning
confidence: 98%